Foamed asphalt, preparation method and application thereof, and cold recycled asphalt mixture
By introducing activated desulfurization glue powder and functional aqueous solution into foam asphalt, a three-phase synergistic action system was constructed, which solved the problems of insufficient interface bonding performance and poor toughness of cold recycled mixtures, and achieved early strength improvements and significant improvements in crack resistance, meeting the technical requirements of the upper layer in asphalt pavement.
Patent Information
- Application Number
- CN202510415647.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-08-01
AI Technical Summary
The existing foam asphalt cold recycled mixtures have problems such as insufficient interface bonding performance, poor toughness and slow development of early strength, resulting in loose structures in the early stage and low use, which limits its promotion and application.
Activated desulfurization rubber powder is introduced as an interface toughening component to build a three-phase synergistic system of water-glue powder-asphalt. By activating the elastic recovery characteristics of desulfurization rubber powder, it forms a dual toughening network with the viscoelastic enhancement effect of petroleum resin, and combines functional aqueous solutions to improve adhesion strength and crack resistance.
Significantly improve the early forming strength and crack resistance of cold regenerated asphalt mixture, and the mechanical properties meet the technical standards of the upper layer in asphalt pavement, achieving efficient recycling and utilization of old materials.
Smart Images

Figure BDA0005343858650000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road construction materials, and particularly relates to a foamed asphalt, a preparation method and application thereof, and a cold recycled asphalt mixture. Background Art
[0002] As a kind of warm mix asphalt binder, foamed asphalt is widely used in the recycling of pavement recycled materials due to its low-carbon environmental protection. Through a special foaming device, asphalt base material, water and air are mixed to form a foam structure, which not only realizes effective bonding with cold and wet aggregates, but also has the advantages of flexibility and anti-fatigue performance. The cold recycling technology based on foamed asphalt can adopt an in-situ construction process, directly using the milled old pavement materials, greatly reducing the raw material transportation link, significantly reducing carbon emissions and engineering costs, and conforming to the concept of green road construction.
[0003] From the perspective of the strength formation mechanism, the initial strength of the foamed asphalt cold recycled mixture mainly depends on the gelling effect of mineral fillers and the interlocking effect of the aggregate skeleton. With the enhancement of the asphalt-aggregate interface bond caused by water loss, its long-term strength shows a progressive increase characteristic. However, this technology still has two core bottlenecks: firstly, the water evaporation rate in the mixture is significantly restricted by environmental temperature and humidity, resulting in an overly long strength development cycle and prone to early structural loosening; secondly, although the rigid enhancement effect of mineral fillers improves the bearing capacity, it makes the mixture lose the functional adaptability of the flexible pavement layer and can usually only be used for the road base structure, causing the "high-value low-use" efficiency reduction of recycled materials and severely restricting the popularization value of this technology. Summary of the Invention
[0004] Aiming at the technical bottlenecks of the existing foamed asphalt cold recycled mixture, such as insufficient interfacial bonding performance, poor toughness and slow initial strength development, the present invention provides a foamed asphalt, a preparation method thereof and an application in a cold recycled asphalt mixture. By introducing activated desulfurized rubber powder as an interfacial toughening component, the bonding performance and crack resistance of the cold recycled asphalt mixture can be effectively improved; at the same time, a new type of functional aqueous solution is developed to replace traditional single water, and a three-phase synergistic action system of water-rubber powder-asphalt is constructed to significantly improve the early forming strength of the cold recycled asphalt mixture. The cold recycled mixture prepared from the foamed asphalt of the present invention not only meets the performance requirements of conventional road bases, but also its mechanical properties and durability indexes can reach the technical standards of the upper middle layer of asphalt pavements, providing a new technical path for the efficient recycling of old materials.
[0005] The technical problems to be solved by the present invention are realized by adopting the following technical solutions:
[0006] One of the purposes of the present invention is to provide a foamed asphalt, which comprises the following components in parts by mass:
[0007] Matrix asphalt 60 - 70 parts
[0008] 18 - 22 parts of activated desulfurized rubber powder
[0009] 4 - 6 parts of petroleum resin
[0010] 3 - 6 parts of functional aqueous solution
[0011] 2 - 3 parts of viscosity reducer
[0012] 0.3 - 0.6 parts of foam stabilizer.
[0013] In the present invention, the softening point of the matrix asphalt is ≥ 45°C, the rotational viscosity at 135°C is ≤ 2 Pa·S, and the residual ductility (10°C) is ≥ 8 cm.
[0014] In the present invention, the activated desulfurized rubber powder is prepared by mechanical shearing and chemical activation of rubber powder. The preparation method is as follows: Soak the rubber powder in a mixed solution of acid and initiator, shear it in a mixer, then add a graft polymer, shear it through a twin - screw extruder, extrude, cool, pelletize, and dry to obtain the activated rubber powder.
[0015] Furthermore, the fineness of the rubber powder is 40 - 60 mesh, the carbon black content is ≥ 28%, and the hydrocarbon content is 42 - 65%.
[0016] Furthermore, the acid is acetic acid, and the volume concentration is ≥ 99.5%.
[0017] Furthermore, the initiator includes but is not limited to dicumyl peroxide, and other common initiators can also be used.
[0018] Furthermore, the mass ratio of the rubber powder to the acid and the initiator is 1:(2 - 6):(3 - 5).
[0019] Furthermore, the soaking time is 5 - 8 h. The acid corrodes the rubber surface to form micropores or uneven structures, enhancing the mechanical anchoring effect with the matrix (such as asphalt, plastic), improving the hydrophilicity of the rubber and its compatibility with polar materials, and enhancing the interfacial bonding strength of the composite material.
[0020] Furthermore, the shear rate of the mixer is 3000 - 4000 r / min, and the shear time is 3 - 4 h.
[0021] Furthermore, the graft polymer includes but is not limited to at least one of maleic anhydride - grafted polyethylene and maleic anhydride - grafted polypropylene.
[0022] Furthermore, the dosage of the graft polymer is 0.3 - 0.6 times the total mass of the rubber powder, the acid, and the initiator.
[0023] Furthermore, the shearing temperature of the twin-screw extruder is 170 - 180 °C, and the shearing time is 20 - 30 min.
[0024] In the present invention, the penetration of high-concentration acetic acid promotes the hardening of rubber molecular chains, thereby improving the mechanical pulverization efficiency of rubber powder in the internal mixer; the initiator can induce the cross-linking and recombination of rubber molecules to form a uniformly distributed microporous network structure; the graft polymer can form a three-dimensional network structure to extend the service life of the material. The grafted flexible chain segments can enhance the elastic recovery ability of the rubber, and the grafted rigid chain segments can improve the hardness and deformation resistance.
[0025] In the present invention, the petroleum resin includes but is not limited to at least one of C5 petroleum resin, C9 petroleum resin, and DCPD petroleum resin.
[0026] In the present invention, the functional aqueous solution is composed of water, sodium silicate, and nano-silica. Preferably, the mass ratio of water, sodium silicate, and nano-silica is 10:(2 - 3):(3 - 5). Sodium silicate is a water-soluble inorganic substance used to improve the internal adhesion of the cold recycled asphalt mixture. The main function of nano-silica is to accelerate water migration, improve the early strength of the cold recycled asphalt mixture, and shorten the strength formation period.
[0027] In the present invention, the viscosity reducer includes but is not limited to at least one of polyethylene wax and chlorinated paraffin.
[0028] In the present invention, the foam stabilizer is diethanolamine. The foam stabilizer can reduce the surface tension of the liquid, making it easier for bubbles to form, while reducing the coalescence and rupture between bubbles. The foam stabilizer can also enhance the strength of the foam film, making the foam more stable and durable. When the foam film is subjected to external impact or vibration, the foam stabilizer can quickly supplement to the surface of the foam film to repair the damaged part, thereby maintaining the stability of the foam.
[0029] The second object of the present invention is to provide a method for preparing the foamed asphalt, comprising the following steps:
[0030] (1) Heat the base asphalt, then add the activated desulfurized rubber powder, petroleum resin, and viscosity reducer, shear, and then add the foam stabilizer and stir to obtain the asphalt binder;
[0031] (2) Add the asphalt binder and the functional aqueous solution into a foaming machine for foaming to obtain the foamed asphalt.
[0032] Furthermore, the shearing rate is 3000 - 4000 r / min, and the time is 60 - 90 min.
[0033] Furthermore, the heating temperature of the base asphalt is 150 - 160 °C.
[0034] The third object of the present invention is to provide the application of the foamed asphalt in the cold recycled asphalt mixture.
[0035] The fourth object of the present invention is to provide a cold recycled asphalt mixture, which includes asphalt pavement recycled materials and the foamed asphalt.
[0036] Furthermore, the mass ratio of the foamed asphalt in the cold recycled asphalt mixture is 3-5%.
[0037] The beneficial effects of the present invention are as follows: Based on the interfacial viscoelastic coupling regulation principle, the present invention constructs a synergistic enhancement system of activated rubber powder-petroleum resin-functional aqueous solution. By using the elastic recovery characteristics of the activated desulfurized rubber powder and the viscoelastic enhancement effect of the petroleum resin to form a double toughening network, the crack resistance and fatigue life of the cold recycled asphalt mixture are significantly improved; through the dual mechanisms of hydrogen bond association and charge adsorption, the functional aqueous solution improves the adhesion strength and anti-stripping ability between the foamed asphalt and the recycled aggregate, improves the internal cohesion of the cold recycled asphalt mixture, and significantly improves the early forming strength of the cold recycled asphalt mixture. Specific Embodiments
[0038] In order to make the technical means, creative features, achieved purposes and effects of the present invention easy to understand, the present invention will be further described below in conjunction with specific embodiments.
[0039] The descriptions of the raw materials in the following examples and comparative examples are as follows:
[0040] Matrix asphalt: 90# asphalt, purchased from Maoming Petrochemical, with a softening point of 47°C, a rotational viscosity at 135°C of 1.532 Pa·S, and a residual ductility (10°C) of 12 cm.
[0041] Rubber powder: with a fineness of 40 mesh, a carbon black content of 31.5%, and a hydrocarbon content of 42%.
[0042] Acetic acid: with a volume concentration of 99.6%.
[0043] Nano-silica: with a particle size of 20 nm.
[0044] Dicumyl peroxide: abbreviated as DCP.
[0045] Polyethylene wax: Polyethylene wax BR-101 purchased from Ninghai Bo'er Chemical Co., Ltd.
[0046] Chlorinated paraffin: 70# chlorinated paraffin purchased from Shandong Yuke Chemical Co., Ltd., CAS: 63449-39-8.
[0047] Example 1
[0048] By mass fraction, there are 60 parts of matrix asphalt, 18 parts of activated desulfurized rubber powder, 4 parts of C9 petroleum resin, 3 parts of functional aqueous solution, 2 parts of polyethylene wax, and 0.3 parts of diethanolamine. Among them, the functional aqueous solution is composed of water, sodium silicate, and nano-silica with a mass ratio of 10:2:3.
[0049] Prepare foamed asphalt according to the above raw material composition and ratio, including the following steps:
[0050] (1) Immerse the rubber powder in a mixed solution of acetic acid and DCP for 6 h. The mass ratio of the rubber powder, acetic acid, and DCP is 1:2:3. Then, shear it in a mixer at 3500 r / min for 3 h. Next, add maleic anhydride grafted polyethylene. The dosage of maleic anhydride grafted polyethylene is 0.3 times the total mass of the rubber powder, acetic acid, and DCP. Shear it through a twin-screw extruder at 175 °C for 30 min, extrude, cool, pelletize, and dry to obtain the activated desulfurized rubber powder.
[0051] (2) Heat the matrix asphalt to 160 °C, then add the activated desulfurized rubber powder, C9 petroleum resin, and polyethylene wax, shear at 3500 r / min for 90 min, and then add diethanolamine and stir to obtain the asphalt binder.
[0052] (3) Add the asphalt binder and the functional aqueous solution to a foaming machine for foaming to obtain foamed asphalt.
[0053] Example 2
[0054] By mass fraction, there are 70 parts of matrix asphalt, 22 parts of activated desulfurized rubber powder, 6 parts of C5 petroleum resin, 6 parts of functional aqueous solution, 3 parts of polyethylene wax, and 0.6 parts of diethanolamine. Among them, the functional aqueous solution is composed of water, sodium silicate, and nano-silica with a mass ratio of 10:3:5.
[0055] Prepare foamed asphalt according to the above raw material formula. The preparation method of foamed asphalt is the same as that in Example 1, except that the mass ratio of the rubber powder, acetic acid, and DCP is 1:6:5, and the dosage of maleic anhydride grafted polyethylene is 0.6 times the total mass of the rubber powder, acetic acid, and DCP.
[0056] Example 3
[0057] By mass fraction, there are 65 parts of matrix asphalt, 20 parts of activated desulfurized rubber powder, 5 parts of DCPD petroleum resin, 5 parts of functional aqueous solution, 3 parts of chlorinated paraffin, and 0.5 parts of diethanolamine. Among them, the functional aqueous solution is composed of water, sodium silicate, and nano-silica with a mass ratio of 10:3:4.
[0058] The preparation of foamed asphalt is carried out according to the above raw material formula. The preparation method of foamed asphalt is the same as that in Example 1, except that the mass ratio of rubber powder, acetic acid and DCP is 1:4:4, and the dosage of maleic anhydride grafted polyethylene is 0.5 times the total mass of rubber powder, acetic acid and DCP.
[0059] Example 4
[0060] By mass, 60 parts of matrix asphalt, 22 parts of activated desulfurized rubber powder, 4 parts of C5 petroleum resin, 6 parts of functional aqueous solution, 2 parts of chlorinated paraffin, and 0.3 part of diethanolamine. Among them, the functional aqueous solution is composed of water, sodium silicate and nano-silica with a mass ratio of 10:3:5.
[0061] The preparation of foamed asphalt is carried out according to the above raw material formula. The preparation method of foamed asphalt is the same as that in Example 1, except that the mass ratio of rubber powder, acetic acid and DCP is 1:6:5, and the dosage of maleic anhydride grafted polyethylene is 0.6 times the total mass of rubber powder, acetic acid and DCP.
[0062] Example 5
[0063] By mass, 70 parts of matrix asphalt, 18 parts of activated desulfurized rubber powder, 6 parts of C9 petroleum resin, 3 parts of functional aqueous solution, 3 parts of polyethylene wax, and 0.6 part of diethanolamine. Among them, the functional aqueous solution is composed of water, sodium silicate and nano-silica with a mass ratio of 10:2:3.
[0064] The preparation of foamed asphalt is carried out according to the above raw material formula. The preparation method of foamed asphalt is the same as that in Example 1, except that the mass ratio of rubber powder, acetic acid and DCP is 1:2:3, and the dosage of maleic anhydride grafted polyethylene is 0.3 times the total mass of rubber powder, acetic acid and DCP.
[0065] Control Example 1
[0066] The preparation of foamed asphalt is carried out according to the raw material formula and preparation method of Example 3, except that the rubber powder is not mechanically sheared and chemically activated, that is, the untreated rubber powder is directly used to replace the activated rubber powder.
[0067] Control Example 2
[0068] The preparation of foamed asphalt is carried out according to the raw material formula and preparation method of Example 3, except that water is used to replace the functional aqueous solution.
[0069] Control Example 3
[0070] The preparation of foamed asphalt is carried out according to the raw material formula and preparation method of Example 3, except that rubber powder is used to replace the activated rubber powder and water is used to replace the functional aqueous solution.
[0071] The recycled asphalt pavement materials are divided into three grades according to particle size: 0 - 5 mm, 5 - 10 mm, and 10 - 15 mm. These three grades of recycled asphalt pavement materials are mixed at a mass percentage of 35%, 35%, and 30%, and then respectively mixed with the foamed asphalt prepared in the above-mentioned examples and control examples. They are cured in a forced-air drying oven at 40°C for 72 h to obtain a cold recycled asphalt mixture with a foamed asphalt mass ratio of 4%. Performance tests are carried out on the foamed asphalt and the cold recycled asphalt mixture, and the test results are shown in Table 1.
[0072] The test methods for expansion ratio and half-life are as follows:
[0073] (1) Record the height h1 of 500 g of asphalt binder before foaming when it is filled into the standard measuring bucket.
[0074] (2) Heat the asphalt binder to 150°C, preheat the foaming machine at 120°C for 20 min, then put the heated asphalt binder into the storage tank of the foaming machine, keep it at 165°C for 30 min, and then introduce the functional aqueous solution.
[0075] (3) Preheat the standard measuring bucket at 120°C for 20 min, vertically place a height standard ruler on the side of the measuring bucket, quickly press the stopwatch after spraying, measure the maximum height h2 of the foamed asphalt, and record the time t1 when the foamed asphalt decays to half of the maximum height at the same time.
[0076] (4) The calculation result of the expansion ratio is h2 / h1, and the half-life is t1.
[0077] The test methods for flexural strain and dry-wet splitting strength refer to the standards JTG E20 T0715 and T0716.
[0078] Table 1
[0079]
[0080] It can be seen from Table 1 that, compared with Control Examples 1 - 3, the expansion ratio of the foamed asphalt prepared in Examples 1 - 5 is ≥15%, and the half-life is ≥13 s; and the flexural strain of the cold recycled asphalt mixture prepared from it is >2700 με, and the dry-wet splitting strength ratio is >80%, meeting the technical requirements of the upper surface layer of the asphalt pavement.
[0081] The above shows and describes the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above-mentioned embodiments. What is described in the above-mentioned embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed. The scope of protection claimed by the present invention is defined by the appended claims and their equivalents.
Claims
1. A foamed asphalt, characterized in that, Comprising the following components in parts by mass: Matrix asphalt: 60 - 70 parts Activated desulfurized rubber powder: 18 - 22 parts Petroleum resin: 4 - 6 parts Functional aqueous solution: 3 - 6 parts Viscosity reducer: 2 - 3 parts Foam stabilizer: 0.3 - 0.6 part.
2. The foamed asphalt according to claim 1, wherein: The softening point of the matrix asphalt is ≥45°C, the rotational viscosity at 135°C is ≤2 Pa·S, and the residual ductility (at 10°C) is ≥8 cm.
3. The foamed asphalt according to claim 1, wherein: The activated desulfurized rubber powder is prepared by mechanical shearing and chemical activation of rubber powder. The preparation method is as follows: Soak the rubber powder in a mixed solution of acid and initiator, shear in a mixer, then add a graft polymer, shear through a twin-screw extruder, extrude, cool, pelletize, and dry to obtain the activated rubber powder.
4. The foamed asphalt according to claim 3, wherein: The fineness of the rubber powder is 40 - 60 mesh, the carbon black content is ≥28%, and the hydrocarbon content is 42 - 65%; Preferably, the acid is acetic acid with a volume concentration ≥99.5%; Preferably, the initiator is dicumyl peroxide; Preferably, the mass ratio of the rubber powder to the acid and the initiator is 1:(2 - 6):(3 - 5); Preferably, the soaking time is 5 - 8 h; Preferably, the shear rate of the mixer is 3000 - 4000 r / min, and the shear time is 3 - 4 h; Preferably, the graft polymer is at least one of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene; Preferably, the dosage of the graft polymer is 0.3 - 0.6 times the total mass of the rubber powder, the acid, and the initiator; Preferably, the shear temperature of the twin-screw extruder is 170 - 180°C, and the shear time is 20 - 30 min.
5. The foamed asphalt according to claim 1, characterized in that: The petroleum resin is at least one of C5 petroleum resin, C9 petroleum resin, and DCPD petroleum resin; Preferably, the viscosity reducer is at least one of polyethylene wax and chlorinated paraffin; Preferably, the foam stabilizer is diethanolamine.
6. The foamed asphalt according to claim 1, characterized in that: The functional aqueous solution is composed of water, sodium silicate, and nano-silica; preferably, the mass ratio of water, sodium silicate, and nano-silica is 10:(2 - 3):(3 - 5).
7. The method for preparing foamed asphalt according to any one of claims 1 to 6, characterized in that, Including the following steps: (1) Heat the matrix asphalt, then add the activated desulfurized rubber powder, petroleum resin, and viscosity reducer, shear, and then add the foam stabilizer and stir to obtain the asphalt binder; (2) Add the asphalt binder and the functional aqueous solution to a foaming machine for foaming to obtain foamed asphalt; Preferably, the shear rate is 3000 - 4000 r / min, and the time is 60 - 90 min; Preferably, the heating temperature of the matrix asphalt is 150 - 160°C.
8. Application of the foamed asphalt according to any one of claims 1 - 6 or the foamed asphalt prepared by the preparation method according to claim 7 in cold recycled asphalt mixture.
9. A cold recycled asphalt mixture, comprising asphalt pavement recycled material and the foamed asphalt according to any one of claims 1 - 6 or the foamed asphalt prepared by the preparation method according to claim 7.
10. The cold recycled asphalt mixture according to claim 9, wherein: The mass proportion of the foamed asphalt in the cold recycled asphalt mixture is 3 - 5%.
Citation Information
Cited By
Composite modified foam cold recycled asphalt mixture based on all-solid waste rubber and preparation method of composite modified foam cold recycled asphalt mixture
CN121698600A